2021
DOI: 10.1002/jcsm.12829
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and skeletal muscle status in patients with head and neck cancer: Impact on outcomes

Abstract: Background Computed tomography (CT)-defined skeletal muscle depletion and malnutrition are demonstrated as poor prognostic factors in patients with head and neck cancer (HNC), however to date, have only been explored in isolation. We aimed to describe body composition profile and examine the impact of nutritional status as well as independently and concurrently occurring body composition features on overall survival, treatment completion, unplanned admissions and length of stay (LOS) in patients undergoing rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…Ideally, sarcopenia thresholds using both sex and BMI‐specific values should be derived specifically using a large population of HNC patients. Although this has not been established to our knowledge to date, the use of the Martin et al 25 thresholds has been demonstrated in an Australian population, with Findlay et al investigating the impact of depleted skeletal muscle on outcomes in a large cohort of 277 patients with HNC 42 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, sarcopenia thresholds using both sex and BMI‐specific values should be derived specifically using a large population of HNC patients. Although this has not been established to our knowledge to date, the use of the Martin et al 25 thresholds has been demonstrated in an Australian population, with Findlay et al investigating the impact of depleted skeletal muscle on outcomes in a large cohort of 277 patients with HNC 42 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously recommended sex‐specific threshold values based on outcomes in HNC populations, however, do not include BMI stratification 37–40 . Although the Martin et al 25 thresholds were derived using a large population of patients with either lung or gastrointestinal cancers ( n = 1473), they have been applied to HNC populations by several authors 32,41–43 . Ideally, sarcopenia thresholds using both sex and BMI‐specific values should be derived specifically using a large population of HNC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only SMI, but also other body (composition) features, e.g. myosteatosis (intramuscular adipose tissue) and BMI (sarcopenic obesity), alone, combined or in combination with nutrition status have a predictive and prognostic value in HNC patients undergoing (chemo)radiotherapy and should be considered in future sarcopenia research [34,38,63].…”
Section: Perspectivesmentioning
confidence: 99%
“…Low SMM is a predictor for the risk of aspiration pneumonia in HNSCC patients receiving chemoradiation ( 78 ). Moreover, low SMM was found to be predictive for length of hospital stay and unplanned admission in HNC patients treated with (chemo)radiotherapy ( 79 ). Low SMM was also associated with long-term morbidity of (chemo)radiation like dysphagia, xerostomia and trismus ( 40 , 80 , 81 ).…”
Section: Sarcopeniamentioning
confidence: 99%